2021
DOI: 10.3390/plants10081717
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Purple Rice Genotypes to Nitrogen and Zinc Fertilizer Application on Grain Yield, Nitrogen, Zinc, and Anthocyanin Concentration

Abstract: Purple rice is recognized as a staple food for humans and as a source of anthocyanins and micronutrients such as zinc (Zn). This study examined how nitrogen (N) and Zn fertilizers affected grain yield and grain N, Zn, and anthocyanin concentration among purple rice genotypes. Six purple rice genotypes (PIZ, KAK, KS, KH-CMU, KDK, and HN) were grown under two levels of N, the optimum N60 (60 kg/ha) and high N180 (180 kg/ha) rates, along with three Zn application methods (no Zn application (Zn0), soil Zn applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
(54 reference statements)
1
5
0
3
Order By: Relevance
“…Moreover, some environmental factors also affect anthocyanin content such as planting area, production system, light, temperature, water and soil properties. Fongfon et al [57] reported that N and Zn fertilizer management was appropriate for purple rice as a guideline to increase yield, N, Zn, and anthocyanin content in grain. A study of Kushwaha [58] revealed that anthocyanin content in black rice increased with an increase in the altitude of the cultivated area.…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…Moreover, some environmental factors also affect anthocyanin content such as planting area, production system, light, temperature, water and soil properties. Fongfon et al [57] reported that N and Zn fertilizer management was appropriate for purple rice as a guideline to increase yield, N, Zn, and anthocyanin content in grain. A study of Kushwaha [58] revealed that anthocyanin content in black rice increased with an increase in the altitude of the cultivated area.…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…Colored rice varieties or genotypes have long been used in traditional foods of Assam and are considered to have medicinal properties by many cultures in Assam 1 and other Asian countries 2 . They are also preferred as a natural source of zinc (Zn) and anthocyanin 3 5 . A wide range of variations in the mineral composition and other many bio-active compounds like flavonoids, polyphenols, and anthocyanins was reported in the colored rice of Assam 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Purple rice with pigmented grains is referred to as black rice in the area where very dark pigment is common and the color is formed by deposits of several compounds located in the pericarp layer, seed coat, or aleurone layer. Purple rice has long been a unique and traditional food and medicinal plant in many cultures 2 , as a natural source of Zn and anthocyanin 3 5 . Purple rice contains secondary compounds such as anthocyanins, flavones, tannins, phenolic acids, sterols, tocols, γ-oryzanols, amino acids, and essential oils; among which anthocyanins account for more than 95% 10 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Salah satunya adalah persilangan antara Padi lokal hitam Pulut Timuru dengan varietas unggul baru padi bersa putih Inpari 42 GSR (belum dipublikasikan). Konsentrasi antosianin dan Zn gabah bervariasi menurut genotip padi (Fongfon et al, 2021). Kandungan Zn bervariasi pada berbagai genotip padi berpigmen (Utasee et al, 2022) (Faiz et al, 2015).…”
unclassified
“…Kandungan Zn bervariasi pada berbagai genotip padi berpigmen (Utasee et al, 2022) (Faiz et al, 2015). Pada genotip-genotip padi berpigmen koleksi negara Thailand menunjukkan variasi dari rendah sampai tinggi yakni 19,0 -41,3 mg kg -1 hasil pembacaan Hitachi Z-8230 Atomic Absorption Spectrophotometer (AAS) (Fongfon et al, 2021;Jaksomsak et al, 2021), dan kandungan Zn yang cukup rendah pada genotip beras berpigmen koleksi yang berasal Lao PDR 15,5 -19,5 mg kg -1 (Xiongsiyee et al, 2018). Namun demikian, studi kaitan warna pigmen beras dengan kandungan zinc belum begitu banyak dilakukan di Indonesia.…”
unclassified